NON-LINEAR ANALYSIS OF SLENDER MASONRY COLUMN SUBJECTED TO BIAXIAL BENDING - Vokál, Marek; Drahorád, Michal (Acta Polytechnica, 2021)
The article deals with a method for analysing slender masonry columns. The proposed method uses material and geometric non-linearity. Various stress-strain diagrams can be used: linear, linear-plastic, parabolic-plastic, two various parabolic and rigid-plastic. In all cases, the tensile strength is neglected. The method can be used for analysing the column in accordance with Eurocodes in two ways: SLS (serviceability limit state) and ULS (ultimate limit state). The internal forces are calculated on a general beam model, with imperfections in both directions, which result in two bending moments in two perpendicular planes – biaxial bending. This case is not covered by the current code – Eurocode, even though all columns are more or less loaded in both directions. In this numerical study, using Matlab software, an algorithm was developed for modelling a real 3D case. The results of this study are also compared to the results of laboratory tests of masonry columns.